Staff Reports of Bullying and Intervention Strategies in Croatian Care and Correctional Institutions for Youth - Sekol, Ivana (International journal of offender therapy and comparative criminology, 2020)
This study compares staff reports of bullying among institutionalized youth with residents' own self-reported prevalence of bullying and victimization collected in the previous study (the Self-Report Study on Bullying in Croatian Residential Care [SSBCRC]) and staff reports of reduction strategies are compared with evidence-based proposed policy solutions arising from residents' reports. The study also compares reduction strategies used by staff with evidence-based proposed policy solutions arising from residents' reports arising from the SSBCRC. A total of 140 staff from 20 Croatian youth facilities completed an anonymous questionnaire. The results revealed that staff estimates of the prevalence of bullying and victimization were significantly lower than resident reports. Staff were better aware of the prevalence of certain types of bullying, but they held stereotypical views of bullies and victims and had difficulties in recognizing the true times and places of bullying. Staff described their anti-bullying policies as being predominantly reactive, rather than proactive and evidence-based. It is concluded that more effort needs to be made to change the current anti-bullying policies used by staff.